Metodología base de gestión de proyectos para una empresa de desarrollo de software - Chacón-Córdoba, Roy Andrés (Instituto Tecnológico de Costa Rica, 2011)
Working with projects, for many companies is a daily affair, but in practice, problems in project management continue to occur in the various projects involved. The software development companies are a typical example, which through the provision of services in the development of projects, must be prepared to avoid repeat or at least minimize such problems, in seeking to achieve successful projects that will allowed to be competitive and keep customers. Through this work was investigated and identified, based on studies and others made by various authors, what are the main reasons leading to problems in software development projects, to which they have faced companies engaged in this type of business. Following this study we identified the following reasons:  Risks were not controlled or re-incorporated in the project.  Incomplete or inadequate information requirements.  Incorporation to change without controls.  Impaired executive support.  Deficiency in planning.  Deficiency in project management.  Lack of definition of roles and responsibilities.  Lack of supervision to the team.  Execution times unrealistic.  Poor communication between staff and involved.  Assignment inadequate in quantity or personal profiles.  Few monitoring and control meetings  Other. On the other hand, with the purpose of the search project success was defined from the literature search and analysis of it, what critical success factors must be considered in the management of software development projects. Product of this research and analysis, it was determined that among the critical factors that must be present for the success of a project, should be considered: support of the sponsor, scope, time, cost, quality, customer satisfaction, development of good relations with stakeholders. However, it is not sufficient to determine the criteria for success of a project, is essential the selection and defining the processes and steps to achieve the objectives, ie the method that will give the guideline to follow to achieve that success. Is therefore, this work defines a methodology based project management software development indicating: stages, processes and steps must be followed, in order to minimize the problems that arise in their management, and also considers the key factors that must be defined to maximize your chance of success. The proposed methodology is based on process groups defined by the Project Management Institute (PMI), and further defines the processes and steps to follow, considering areas such as: Integration, Scope, Time, Cost, Quality, Human Resources, Communications and Risks.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área acádemica de Gerencia de Proyectos, Escuela de Administración de Empresas, 2011.
Keywords: Herramientas; Calidad; Riesgos; Recursos humanos; Gestión de la producción; Gestión de calidad; Comunicación